The Influence of SV40 polyA on Gene Expression of Baculovirus Expression Vector Systems. - Tamer Z Salem; Craig P Seaborn; Colin M Turney; Jianli Xue; Hui Shang; Xiao-Wen Cheng (PLoS ONE)
The simian virus 40 polyadenylation signal (SV40 polyA) has been routinely inserted downstream of the polyhedrin promoter in many baculovirus expression vector systems (BEVS). In the baculovirus prototype Autographa californica multiple nucleopolyhedrovirus (AcMNPV), the polyhedrin promoter (very late promoter) transcribes its gene by a viral RNA polymerase therefore there is no supporting evidence that SV40 polyA is required for the proper gene expression under the polyhedrin promoter. Moreover, the effect of the SV40 polyA sequence on the polyhedrin promoter activity has not been tested either at its natural polyhedrin locus or in other loci in the viral genome. In order to test the significance of adding the SV40 polyA sequence on gene expression, the expression of the enhanced green fluorescent protein (egfp) was evaluated with and without the presence of SV40 polyA under the control of the polyhedrin promoter at different genomic loci (polyherin, ecdysteroid UDP-glucosyltransferase (egt), and gp37). In this study, spectrofluorometry and western blot showed reduction of EGFP protein for all recombinant viruses with SV40 polyA, whereas qPCR showed an increase in the egfp mRNA levels. Therefore, we conclude that SV40 polyA increases mRNA levels but decreases protein production in the BEVS when the polyhedrin promoter is used at different loci. This work suggests that SV40 polyA in BEVSs should be replaced by an AcMNPV late gene polyA for optimal protein production or left untouched for optimal RNA production (RNA interference applications).